(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This study analyzes the intersection between renewable engineering, digitalization and automation, and how their synergy can promote social transformation towards sustainable development. Through a systematic review of recent literature (2020–2025), the technical mechanisms (smart control, smart grids, predictive analytics), the effects on energy efficiency and demand, as well as the social impacts —positive and risk— associated with technological adoption were identified. Benefits are evident in the integration of variable sources, operational optimization and cost reduction, but also challenges linked to equity, data governance and the energy demand of digital systems. Recommendations for public policies, participatory models and future research agenda focused on digital energy justice are proposed.